2016
DOI: 10.1111/1744-7917.12290
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of peptidoglycan recognition proteins in endoparasitoid wasp Microplitis mediator

Abstract: Peptidoglycan recognition proteins (PGRPs) are a family of innate immune receptors that specifically recognize peptidoglycans (PGNs) on the surface of a number of pathogens. Here, we have identified and characterized six PGRPs from endoparasitoid wasp, Microplitis mediator (MmePGRPs). To understand the roles of PGRPs in parasitoid wasps, we analyzed their evolutionary relationship and orthology, expression profiles during different developmental stages, and transcriptional expression following infection with G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…This indicated that BdPGRP-SA can be induced by E. coli and S. aureus (Figure 4). The inducible expression of PGRPs has been observed in Armigeres subalbatus [45], A. aegypti [41], and Microplitis mediator [46]. The induction of BdPGRP-SA and -SD by PGN-EB was confirmed earlier [47].…”
Section: Discussionmentioning
confidence: 65%
“…This indicated that BdPGRP-SA can be induced by E. coli and S. aureus (Figure 4). The inducible expression of PGRPs has been observed in Armigeres subalbatus [45], A. aegypti [41], and Microplitis mediator [46]. The induction of BdPGRP-SA and -SD by PGN-EB was confirmed earlier [47].…”
Section: Discussionmentioning
confidence: 65%
“…dsRNA was synthesized from specific gene templates according to a previously described method ( 62 ). The GFP gene was used as the control.…”
Section: Methodsmentioning
confidence: 99%
“…The phylogenetic tree was constructed using the neighbour-joining algorithm, enger receptors (Yu et al, 2002;Lemaitre & Hoffmann, 2007;Ragan et al, 2009;Sumathipala & Jiang, 2010;Bang et al, 2013Bang et al, , 2022. As a member of the PRP family, PGRP only recognizes molecules on the surface of pathogenic organisms and then selectively activates pathways such as the Toll pathway, immune defi ciency (IMD) pathway, JAK-STAT pathway and reactive oxygen species metabolism or blackening reaction to kill the pathogens Huang et al, 2015;Wang et al, 2016;Lu et al, 2019;Hou et al, 2020;Wei et al, 2020).…”
Section: Phylogenetic Analysismentioning
confidence: 99%